Reciprocal Associations Between Sleep, Mental Strain, and Training Load in Junior Endurance Athletes and the Role of Poor Subjective Sleep Quality - Hrozanova, Maria; Klöckner, Christian A.; Sandbakk, Øyvind; Pallesen, Ståle; Moen, Frode (Frontiers in Psychology, 2020)
The importance of adequate sleep for athletic functioning is well-established. Still, the literature shows that many athletes report sleep of sub-optimal quality or quantity. To date, no research has investigated how bidirectional variations in mental and physiological states influence sleep patterns. The present study therefore investigated reciprocal associations between sleep, mental strain and training load by utilizing a prospective, observational design. In all, 56 junior endurance athletes were followed over 61 consecutive days. Unobtrusive, objective measurements of sleep with novel radar technology were obtained, and subjective daily reports of mental strain and training load were collected. The role of subjective sleep quality was investigated to identify whether the reciprocal associations between sleep, mental strain and training load depended on being a good vs. poor sleeper. Multilevel modeling with Bayesian estimation was used to investigate the relationships. The results showed that increases in mental strain were associated with decreased total sleep time (TST, 95% CI=-.12 to -.03), light sleep (95% CI=-.08 to -.00) and sleep efficiency (95% CI=-.95 to -.09). Further, both mental strain and training load were associated with subsequent deceased rapid eye movement (REM, respectively 95% CI=-.05 to -.00 and 95% CI=-.06 to -.00) sleep. Increases in TST, light, deep and REM sleep were all associated with subsequent decreased training load (respectively 95% CI= -.09 to -.03; 95% CI= -.10 to -.01; 95% CI= -.22 to -.02; 95% CI= -.18 to -.03). Finally, among poor sleepers, increases in sleep onset latency were associated with increases in subsequent mental strain (95% CI= .09 to .46), and increases in deep sleep were associated with decreases in subsequent training load (95% CI=-67.65 to 11.43). These results offer novel insight into the bidirectional associations between sleep, mental strain and training load in athletes, and demonstrate detrimental effects of mental strain on sleep, likely caused by mental activation incompatible with sleep. An increased need for recovery, suggested by increased TST and time in different sleep stages, was associated with subsequent self-regulatory reduction of training loads by the athletes. In poor sleepers, increases in deep sleep may suggest an elevated need for physiological recovery.